Impaired sustained attention in groups at high risk for antisocial personality disorder: A contingent negative variation and standardized low-resolution tomographic analysis study - Guan, Muzhen; Ma, Lifang; Zhu, Yifang; Liao, Yang; Zeng, Lingwei; Wu, Shengjun; Men, Ke; Liu, Xufeng (Frontiers in Human Neuroscience, 2022)
Objective This study aimed to explore the characteristics of contingent negative variation (CNV) in groups at high risk for antisocial personality disorder. Materials and methods A classic CNV paradigm was used to compare the characteristics of attention maintenance among a group of individuals with conduct disorder (CD group; n = 27), a group of individuals with antisocial personality traits (AP; n = 29), a group of individuals with conduct disorder and antisocial personality traits (CD + AP group; n = 25), and a group of healthy controls (CG group; n = 30), to examine the characteristics of the amplitude and latency of CNV in different processing stages. Results Results of the event-related potential analysis were as follows: The mean amplitude analysis between 500 and 1,000 ms revealed that the mean CNV amplitudes in the CD + AP group (-1.388 ± 0.449 μV, P < 0.001) were significantly lower than that in the CG group (-4.937 ± 0.409 μV). The mean amplitude analysis between 1,000 and 1,500 ms revealed that the mean CNV amplitude in the CD + AP group (-0.931 ± 0.646 μV) was significantly lower than that in the CG group (4.809 ± 0.589 μV, P < 0.001). The mean amplitude analysis between 1,500 and 2,000 ms revealed that the mean CNV amplitude in the CG group (3.121 ± 0.725 μV) was significantly higher than that in the CD + AP group (-0.277 ± 0.795 μV, P = 0.012), whereas the mean CNV amplitude in the CD + AP group was not significantly different in the AP group (P = 0.168) and CD group (P > 0.05). Source localization results indicated altered activity in frontal-temporal regions. Conclusion The CNV amplitude characteristics in the CD + AP group and AP group were more consistent and fluctuated around the baseline, indicating the absence of attention maintenance resulted in impairments in attention allocation and motor preparation in the CD + AP group and AP group.